The Effectiveness of Round-Robin Techniques Aided with Guided Questions on Reading Comprehension - Lestari, Erma Rahayu (Jurnal Pendidikan Bahasa Inggris Proficiency, 2025)
This study evaluates the impact of the round-robin technique with guided questions on reading comprehension among 8th-grade students at SMPN 1 Jogoroto Jombang. Using a quasi-experimental design, the research compared two groups: one using round-robin with guided questions (29 students) and the other using round-robin alone (26 students). Pre-tests and post-tests assessed reading comprehension. ANCOVA analysis showed a significance value of 0.655, indicating no significant difference between the two groups. The study found that covariates like prior English knowledge and vocabulary mastery were influential. Therefore, these factors should be considered when implementing the round-robin technique.